Quality of life of breast cancer patients - Anggraeni, Feny Dwi; Sukartini , Tintin; Nihayati, Hanik Endang (Universitas Airlangga, 2023)
Introduction: Breast cancer is a type of cancer with the highest incidence among women worldwide. It has an impact on the patient's physical, psychological, social, and functional health. Breast cancer patients have a greater burden of symptoms, which can lead to decreased quality of life. This study had the objective to describe breast cancer patients' quality of life in a hospital.Methods: A descriptive observational study design was used. The research population was breast cancer patients in a public hospital. The sample in this study was based on the inclusion and exclusion criteria, with a total of 110 respondents obtained through the proportional sampling technique. The data were analyzed using descriptive analysis. Data were collected by referencing demographic data and distributing a quality-of-life questionnaire (FACT-B). Results: Regarding the quality-of-life variable, findings show that 32 patients had very bad physical well-being (29.1%). Most of the social well-being relations were good, with 40 respondents in this category (36.4%). The majority were in the bad category in terms of functional well-being, with 52 respondents being identified (47.3%). Emotional well-being was considered good for 66 respondents (60.0%). In terms of additional concerns, as many as 60 respondents were in the bad category (54.2%).Conclusions: Chronic conditions can negatively impact patients' physical health and quality of life. Low quality of life is related to the burden of symptoms experienced by patients, such as anxiety, depression, and fatigue. This suggests that social support can strengthen effective coping and improve patients' quality of life.Keywords: breast cancer; breast carcinoma; health-related quality of life; quality of life; patients